4(2p+3)=3+8(p-8)

Simple and best practice solution for 4(2p+3)=3+8(p-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2p+3)=3+8(p-8) equation:


Simplifying
4(2p + 3) = 3 + 8(p + -8)

Reorder the terms:
4(3 + 2p) = 3 + 8(p + -8)
(3 * 4 + 2p * 4) = 3 + 8(p + -8)
(12 + 8p) = 3 + 8(p + -8)

Reorder the terms:
12 + 8p = 3 + 8(-8 + p)
12 + 8p = 3 + (-8 * 8 + p * 8)
12 + 8p = 3 + (-64 + 8p)

Combine like terms: 3 + -64 = -61
12 + 8p = -61 + 8p

Add '-8p' to each side of the equation.
12 + 8p + -8p = -61 + 8p + -8p

Combine like terms: 8p + -8p = 0
12 + 0 = -61 + 8p + -8p
12 = -61 + 8p + -8p

Combine like terms: 8p + -8p = 0
12 = -61 + 0
12 = -61

Solving
12 = -61

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 24x^2+41x+12=0 | | -3(1-4k)=3(-1+7k)-5k | | 24x^2+41y+12=0 | | 7b^2-14b-55=0 | | -3(-5n+1)=3(6n-8) | | 9=7p-5p+7 | | y^2=10-6x^2 | | 9x-4=3x-16 | | 3x+5+6x-2=39 | | 4x^3-9x^2+6x=0 | | -2n=3n | | 5n-10=0 | | 40r+48s= | | 9r^2-49=0 | | -6(8+4n)+5(1+4n)=-11 | | 5(b-4)=12 | | -6(8+4n)+5(1+4n)=-1 | | p+.33p=.67 | | 41*8.98= | | 2r^2+7r^2-2r^2= | | x^2-x-14=3x-2 | | 3x+34-x+3=1 | | 8(5k-4)+3(-8k-6)=30 | | 2x^2+16x+42=0 | | 7(2-x)=5x | | 4x^7-20x^6+8x^5=0 | | 8(y-2)+6=2(y+1) | | x^2+6x+13=5 | | 3(2x-4)=3 | | 3w^2+12w+30=0 | | 12(7c+2)= | | Solvey=2x-3 |

Equations solver categories